2013
DOI: 10.5424/sjar/2013113-3753
|View full text |Cite
|
Sign up to set email alerts
|

Sort communication. Genotype × environment interaction analysis in two chickpea RIL populations

Abstract: In order to introduce new chickpea germplasm in Argentina, two recombinant inbred line (RIL) populations F6:7 of twenty lines, each one derived from crosses between kabuli and desi types, were evaluated for yield components in different sites and years. Additive main effects and multiplicative interaction (AMMI) analysis was applied to study the performance of different genotypes in different environments. Genotype (G), environment (E) and GE interaction effects were highly significant in both populations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Experimental material responded differently to varying environmental conditions implying that for achieving sustainability inchickpea production; studies pertaining to G×E interactions should be an integral part of chickpea improvement plans. G×E interaction showed the significant differences for DM,BY and SY indicates differential response of the genotype to different planting conditions in close harmony with Singh and Singh (2013), Carreras et al, (2013) and Tilihun et al, (2015) for DM, BY and SY.The variance due to environment found significant for all the characters except DM however, environment linear was observed significant for all the characters. (Table 1) G×E (linear) showed the significant differences for DM,DF 50%, BY and SY suggested that prediction for these attributes would be perfect, these results supporting the earlier findings of Tilihun et al, (2015), Kanouni et al, (2015) and Tilihun et al, (2015).…”
Section: Resultssupporting
confidence: 69%
“…Experimental material responded differently to varying environmental conditions implying that for achieving sustainability inchickpea production; studies pertaining to G×E interactions should be an integral part of chickpea improvement plans. G×E interaction showed the significant differences for DM,BY and SY indicates differential response of the genotype to different planting conditions in close harmony with Singh and Singh (2013), Carreras et al, (2013) and Tilihun et al, (2015) for DM, BY and SY.The variance due to environment found significant for all the characters except DM however, environment linear was observed significant for all the characters. (Table 1) G×E (linear) showed the significant differences for DM,DF 50%, BY and SY suggested that prediction for these attributes would be perfect, these results supporting the earlier findings of Tilihun et al, (2015), Kanouni et al, (2015) and Tilihun et al, (2015).…”
Section: Resultssupporting
confidence: 69%
“…Inheritance of seed size was demonstrated to be monogenic 86 and polygenic 84 , 87 – 89 through different studies. Although seed size in chickpeas has a high heritability 84 , 90 – 92 , it is not only affected by genetic factors but also by the environment 14 , 17 , 44 , 93 . In terms of seed size, many genotypes (209 genotypes) with larger seeds than large-seeded parents were determined (Tables 2 , 3 , Fig.…”
Section: Discussionmentioning
confidence: 99%